Drying of red ceramic brick. Effect of five silicone-based water-repellent treatments. - Couto, S. (2011)
The presence of moisture inside a material whose surface was treated with a water repellent agent may give rise to unwanted side-effects. Indeed, the temporal and spatial significance of moistening events may be intensified if a water-repellent, as any other kind of treatment, hinders drying. This effect can be particularly relevant for historical buildings, where moisture from varied origins is recurrently present in the masonry, but is also pertinent for more recent constructions since water often finds ways to penetrate the building elements, through cracks or joints. This article discusses the application of water repellent treatments on ceramic brick, with regard to drying of the masonry. The influence of cracks parallel or perpendicular to the surface is taken into account. Five silicone-based treatments were studied. The treated or untreated material was subjected to capillary absorption tests by which the effectiveness of the water repellent effect was estimated, as well as water vapour permeability tests and drying tests. The effectiveness of four out of the five treatments is high. Vapour permeability is not much affected in one case, when the cracks are parallel to the surface, and in none of the cases, when they are perpendicular. Nonetheless, drying is significantly delayed by any of the five products, both in the case where the cracks are parallel to the surface as when they are perpendicular.